2017
DOI: 10.1167/iovs.16-20659
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Photosensitive Retinal Ganglion Cell Function, Sleep Efficiency and Depression in Advanced Age-Related Macular Degeneration

Abstract: Citation: Maynard ML, Zele AJ, Kwan AS, Feigl B. Intrinsically photosensitive retinal ganglion cell function, sleep efficiency and depression in advanced age-related macular degeneration. Invest Ophthalmol Vis Sci. 2017;58:990-996. DOI:10.1167/ iovs.16-20659 PURPOSE. Melanopsin expressing intrinsically photosensitive retinal ganglion cells (ipRGC) input to multiple brain regions including those for pupil control, circadian rhythms, sleep and mood regulation. Here we measured ipRGC function and its relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 72 publications
0
59
0
Order By: Relevance
“…Reduced nocturnal synthesis of melatonin and sleep disturbance in AMD have been reported in the literature (Rosen et al 2009;Khurana et al 2016;Lv et al 2016;P erez-Canales et al 2016;Maynard et al 2017). Compared with age-and gender-matched controls, Rosen et al (2009) found 40% lower level of urinary 6-sulfatoxymelatonin (aMT6s), major metabolite of melatonin, in patient with AMD.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Reduced nocturnal synthesis of melatonin and sleep disturbance in AMD have been reported in the literature (Rosen et al 2009;Khurana et al 2016;Lv et al 2016;P erez-Canales et al 2016;Maynard et al 2017). Compared with age-and gender-matched controls, Rosen et al (2009) found 40% lower level of urinary 6-sulfatoxymelatonin (aMT6s), major metabolite of melatonin, in patient with AMD.…”
Section: Introductionmentioning
confidence: 94%
“…Short (<6 hr) and long (>8 hr) sleep duration per night are independently associated with exudative AMD and geographic atrophy, respectively (Khurana et al 2016;P erez-Canales et al 2016). Poor sleep efficiency in patients with advanced AMD was also observed (Maynard et al 2017).…”
Section: Introductionmentioning
confidence: 95%
“…This could explain why DME was associated with high risk for insomnia but not short sleep duration in our study. mRGC loss and dysfunction have previously been shown in macular disease such as DME and agerelated macular degeneration [26,34]. On the other hand, insomnia might contribute to the development of DME through other mechanisms such as hyperarousals and increased serum cortisol and adrenocorticotrophic hormone levels [33,35,36].…”
Section: Discussionmentioning
confidence: 95%
“…The reduction in the post-illumination pupil response amplitude (closer to baseline diameter) in the PD group compared to controls indicates that melanopsin-mediated ipRGC inputs to pupil control pathway are impaired, and that this effect size is both large and clinically relevant (difference between medians = 17.49%). Reduced ipRGC function has been associated with impaired sleep in retinal diseases (Gracitelli et al ., 2015, Maynard et al ., 2017) and while there was reduced sleep quality in patients with Parkinson’s disease compared to the control group, this difference was not statistically significant. We acknowledge however that alternative methods of sleep assessment such as polysomnography may be more sensitive than the PSQI in detecting sleep deficits.…”
Section: Discussionmentioning
confidence: 99%